The Efficacy of Salvia officinalis on the Prevention of Recurrent Vulvovaginal Candidiasis: A Randomized, Controlled Clinical Trial - Ahangari, Fatemeh; Oskouei, Behnaz S.; Javadzadeh, Yousef; Adibpour, Mohammad; Farshbaf-Khalili, Azizeh (Current Women's Health Reviews, 2023)
Background: In addition to physical discomfort, recurrent vulvovaginal candidiasis imposes a significant financial and psychosocial burden, such as lower levels of self-esteem, a higher level of stress, clinical depression, and less satisfaction with their life. Recurrent vulvovaginal candidiasis interferes with emotional and sexual relationships. Objective: This study aimed to compare the effect of vaginal Salvia officinalis, clotrimazole, and their combination on the prevention of recurrent vulvovaginal candidiasis. Methods: This randomized triple-blinded trial was conducted on 111 women aged 18-49 years with vulvovaginal candidiasis. Participants were randomly assigned into one of the three groups of vaginal tablets of Salvia officinalis 400 mg and placebo of clotrimazole 100 mg, clotrimazole 100 mg and placebo of Salvia officinalis 400 mg, or Salvia officinalis and clotrimazole that were applied every night for 7 consecutive days. A recurrence rate of vulvovaginal candidiasis was evaluated by WET test and vaginitis symptoms examination after 12 weeks. In the case of positive evaluation, the culture of vaginal discharge was performed. Results: Totally, 29 patients (80.6%) in group clotrimazole, 33 patients (94.3%) in group Salvia officinalis and 35 patients (97.2%) in group Salvia officinalis-clotrimazole were treated (P = 0.43). Out of cured patients, 4 (13.8%) patients in the group clotrimazole, 1 patient (3%) in group Salvia officinalis, and no case in group Salvia officinalis-clotrimazole experienced the recurrence of infection. There was a significant difference among the 3 groups in terms of recurrence (P = 0.023). Moreover, no adverse event during the 12 weeks after treatment was observed. Conclusion: Adjuvant therapy of Salvia officinalis alongside routine vaginal clotrimazole could successfully prevent recurrent vulvovaginal candidiasis after three months.
Keywords: Salvia officinalis